Maintaining sagittal plane balance compromises frontal plane balance during reactive stepping in people post-stroke. (December 2020) - Buurke, Tom J.W.; Liu, Chang; Park, Sungwoo; den Otter, Rob; Finley, James M.
Abstract: Background. Maintaining balance in response to perturbations during walking often requires the use of corrective responses to keep the center of mass within the base of support. The relationship between the center of mass and base of support is often quantified using the margin of stability. Although people post-stroke increase the margin of stability following perturbations, control deficits may lead to asymmetries in regulation of margins of stability, which may also cause maladaptive coupling between the sagittal and frontal planes during balance-correcting responses. Methods . We assessed how paretic and non-paretic margins of stability are controlled during recovery from forward perturbations and determined how stroke-related impairments influence the coupling between the anteroposterior and mediolateral margins of stability. Twenty-one participants with post-stroke hemiparesis walked on a treadmill while receiving slip-like perturbations on both limbs at foot-strike. We assessed anteroposterior and mediolateral margins of stability before perturbations and during perturbation recovery. Findings . Participants walked with smaller anteroposterior and larger mediolateral margins of stability on the paretic versus non-paretic sides. When responding to perturbations, participants increased the anteroposterior margin of stability bilaterally by extending the base of support and reducing the excursion of the extrapolated center of mass. The anteroposterior and mediolateral margins of stability in the paretic limb negatively covaried during reactive steps such that increases in anteroposterior were associated with reductions in mediolateral margins of stability. Interpretation . Balance training interventions to reduce fall risk post-stroke may benefit from incorporating strategies to reduce maladaptive coupling of frontal and sagittal plane stability. Highlights: Post-stroke sensorimotor impairments lead to asymmetric margins of stability We asked how people post-stroke regulate margins of stability during slip recovery We found smaller anteroposterior & larger mediolateral paretic margins of stability Increased forward margins coincided with decreases in mediolateral margins